1979
DOI: 10.1136/oem.36.4.292
|View full text |Cite
|
Sign up to set email alerts
|

Oral and pharyngeal cancer in the North-west and West Yorkshire regions of England, and occupation.

Abstract: (1974) found a 77% excess of deaths from oral and pharyngeal cancers in male textile workers compared with the male population of England and Wales. This finding was based on the 31 deaths from oral and pharyngeal cancer of male textile workers aged 15-64 yr in 1959-63. Using this group, together with further data, they also showed that the excess appeared to be greatest in wool-fibre preparers. However, they advised caution about this conclusion which was based on a single set of numerators and compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1
1

Year Published

1980
1980
2002
2002

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 7 publications
0
5
1
1
Order By: Relevance
“…Some of the suggested associations with categories of production workers also confirmed the results of previous reports. Oral and pharyngeal cancer risk has been associated with work in the textile and apparel manufacturing industry (19)(20)(21)(22)(23)(24), even if other reports (25,26) did not confirm the finding. Machinists and metal working machine operators (18,27), miners (24), workers in the building industry (24), painters (18), plumbers (27), printers (15,28), electronics manufacturing workers (26,29) and electricity production workers (30), and different categories of railway workers (13,15) have previously been suggested to be at increased risk.…”
Section: Discussioncontrasting
confidence: 43%
“…Some of the suggested associations with categories of production workers also confirmed the results of previous reports. Oral and pharyngeal cancer risk has been associated with work in the textile and apparel manufacturing industry (19)(20)(21)(22)(23)(24), even if other reports (25,26) did not confirm the finding. Machinists and metal working machine operators (18,27), miners (24), workers in the building industry (24), painters (18), plumbers (27), printers (15,28), electronics manufacturing workers (26,29) and electricity production workers (30), and different categories of railway workers (13,15) have previously been suggested to be at increased risk.…”
Section: Discussioncontrasting
confidence: 43%
“…Relationships with both alcohol In our study 9 either mode1 adequately described the and smoking have been well documented in other data. To distinguish between them empirically in hustudies (Grahametal., 1977;Wynderetal., 1956Wynderetal., ,1957, man studies is difficult as in this population as in most 1976; Bross and Coombs, 1976;Feldman and Boxer, others smoking and alcohol consumption are highly 1979;Herity et al, 1981;Hinds et al, 1979;Keller and Terris, 1965;Martinez, 1969;Rothman and Keller, Our results show that smoking is a less important 1972; Smith, 1979;Whitaker et al, 1979). Our results factor than alcohol consumption.…”
Section: Smoking Ciddaymentioning
confidence: 59%
“…Mashberg and Meyers (1976) in a prospective study showed no direct association of the site of dental irritation with that of the tumour. Less detailed studies assessing the use of dentures or edentia have been inconsistent (Whitaker et al, 1979;Herity etal., 1981). Wynder el al.…”
Section: Smoking Ciddaymentioning
confidence: 99%
“…Similarly, although some authors have found an increased risk of laryngeal or pharyngeal cancers among textile workers,7-9 47 other studies have failed to confirm these results 1335 39 48 Moreover, most textile or wood workers are exposed not only to wood dust or textile dust, but also to numerous other substances, including solvents, varnishes, dyes, asbestos, and formaldehyde 3749 50These other substances can all be potential confounders in studies based on job titles.…”
Section: Discussionmentioning
confidence: 99%